Knowledge and Innovation Management to Support Supply Chain Innovation and Sustainability Practices. Issue 1 (2nd January 2022) - Gloet, Marianne; Samson, Danny
ABSTRACT: This paper extends exploratory research on the contribution of knowledge and innovation management (KIM) to innovation and sustainability activities across a number of small to medium size Australian food and beverage exporters in Australia, as part of a longitudinal research study. Recent trends in sustainable supply chain management (SSCM) in global supply chains see a greater focus on achieving more social and transformational forms of sustainability, in addition to traditional economic or environmental approaches.